1993
DOI: 10.1128/aem.59.2.358-364.1993
|View full text |Cite
|
Sign up to set email alerts
|

The Mode of Replication Is a Major Factor in Segregational Plasmid Instability in Lactococcus lactis

Abstract: The effects of the rolling-circle and theta modes of replication on the maintenance of recombinant plasmids in Lactococcus lactis were studied. Heterologous Escherichia coli or bacteriophage A DNA fragments of various sizes were inserted into vectors based on either the rolling-circle-type plasmid pVVO1 or the theta-type plasmid pAM,l. All pAM1il derivatives were stably maintained. pVV01 derivatives, however, showed size-dependent segregational instability, in particular when large DNA fragments were inserted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(37 citation statements)
references
References 36 publications
0
37
0
Order By: Relevance
“…For overexpression of ␣-amylase, integrant strains harboured plasmid pKTH10 (Table 1). The integration constructs used and the resulting mutant chromosomes ᮊ 1999 Blackwell Science Ltd, Molecular Microbiology, 31, 533-543 Em r , pAM␤1 replication origin Kiewiet et al (1993) are shown schematically in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…For overexpression of ␣-amylase, integrant strains harboured plasmid pKTH10 (Table 1). The integration constructs used and the resulting mutant chromosomes ᮊ 1999 Blackwell Science Ltd, Molecular Microbiology, 31, 533-543 Em r , pAM␤1 replication origin Kiewiet et al (1993) are shown schematically in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…1991. Assays for segregational plasmid stability were performed as described by Kiewiet et al (1993).…”
Section: Copy Number Determination Detection Of Single-stranded Dna mentioning
confidence: 99%
“…This result reveals that the mode of plasmid replication determines consistent stability both in P-and F-cells regardless of the presence of cryptic plasmid. Kiewiet et al (1993) reported that the theta-type plasmids are segregationally stable in host cells and we have found that the pCB vector replicate by theta-type replication mode .…”
Section: Plasmid Segregational Stabilitymentioning
confidence: 62%